Unemployment and dimensions of subjective health: exploring moderating effects of age - Maslić Seršić, Darja (Array, 2005)
We compare different age groups of unemployed persons and general population on eight dimensions of physical, psychological and general subjective health. Subjective health was assessed by the Croatian version of the SF-36 Health Survey on national samples of registered unemployed persons (n=1, 138) and of the general population (n=5048). Compared to the general population, the unemployed persons achieved significantly lower results on all dimensions of psychological health, while their physical and general health was similar to that of the general population. All aspects of subjective health deteriorate with age in both groups. Emotional health decreases even faster in the sample of the unemployed, and reaches its minimum in the middle age group. The longer the unemployment lasts, the more negative is the effect of age on general health, emotional health and social functioning. We conclude that aging is a significant predictor of the amount of negative consequences of unemployment, and has an especially important role in decreased social and emotional functioning of the unemployed.